2016
DOI: 10.3389/fphys.2016.00367
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Myocardial Composition and Conduction Properties in Rat Heart Failure Model Induced by Chronic Volume Overload

Abstract: Volume overload leads to development of eccentric cardiac hypertrophy and heart failure. In our previous report, we have shown myocyte hypertrophy with no fibrosis and decrease in gap junctional coupling via connexin43 in a rat model of aorto-caval fistula at 21 weeks. Here we set to analyze the electrophysiological and protein expression changes in the left ventricle and correlate them with phenotypic severity based upon ventricles to body weight ratio. ECG analysis showed increased amplitude and duration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…where D is a scalar value that is set to 1.8 × 10 −2 mm 2 /ms in the 1D tissue model, giving a transmural CV of 19.84 cm/s, within the measured range of 14.6 to 102 cm/s in rat ventricular tissues (Sedmera et al, 2016). As the ventricular wall in rat heart is rather thin, a length of 3 mm of transmural 1D strand was constructed with 2 mm designated as endocardial and 1 mm epicardial tissues, which was inconsistent with our previous study (Zhang et al, 2009).…”
Section: Transmural Ventricular Tissue Modelmentioning
confidence: 80%
“…where D is a scalar value that is set to 1.8 × 10 −2 mm 2 /ms in the 1D tissue model, giving a transmural CV of 19.84 cm/s, within the measured range of 14.6 to 102 cm/s in rat ventricular tissues (Sedmera et al, 2016). As the ventricular wall in rat heart is rather thin, a length of 3 mm of transmural 1D strand was constructed with 2 mm designated as endocardial and 1 mm epicardial tissues, which was inconsistent with our previous study (Zhang et al, 2009).…”
Section: Transmural Ventricular Tissue Modelmentioning
confidence: 80%
“…Like other components of the VCS, Purkinje fibers highly express Connexin 40 (Cx40, encoded by Gja5). Furthermore, altered expression of Cx40 and Connexin 43 (Cx43) have been observed in mouse and human cardiomyopathies with aberrant ventricular conduction [13][14][15][16]. To investigate this potential mechanism of abnormal ventricular conduction in cardiomyocyte S1pr1 mutant mice, we first assessed Cx40 expression in hearts from mice at 15.5 dpc.…”
Section: Ventricular Conduction System Development After Embryonic Camentioning
confidence: 99%
“…Cardiomyocytes within the VCS highly express Connexin 40 (Cx40), while both VCS and working myocardium express Connexin 43 (Cx43) [12]. Abnormal expression of either Cx40 or Cx43 have been reported in patients with ventricular conduction disease, and mouse models support roles for both connexins in normal ventricular conduction [13][14][15][16]. Of note, Purkinje fibers originate from trabecular myocardium, and how the persistence of trabecular myocardium affects the VCS and working myocardium is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a significant increase in the number of studies concerned with the molecular mechanism of hypertrophy, especially in concentric hypertrophy induced by pressure overload . However, the molecular regulation mechanism of eccentric hypertrophy caused by volume overload is still not fully understood …”
Section: Introductionmentioning
confidence: 99%
“…4 However, the molecular regulation mechanism of eccentric hypertrophy caused by volume overload is still not fully understood. 5 MURC (a muscle-restricted coiled-coil protein), also called Cavin-4 (caveolae-associated protein 4), is a cytosolic protein and the fourth member of the Cavin family. 6 A recent study showed that MURC could interact with Cavin-1, Cavin-2 and Cavin-3 to form caveolae.…”
Section: Introductionmentioning
confidence: 99%